The validity and clinical utility of the Massachusetts Youth Screening Instrument – version 2 (MAYSI‐2) in the UK. (11th August 2014) - Lennox, Charlotte; O'Malley, Kate; Bell, Vicky; Shaw, Jenny; Dolan, Mairead
ABSTRACT Background The Massachusetts Youth Screening Instrument – version 2 (MAYSI‐2) is designed to assist in identifying the mental health needs of young people admitted to secure establishments. To date, very few studies have assessed the MAYSI‐2 outside the USA. Aims This study aimed to assess the validity and clinical utility of the MAYSI‐2 in England. Methods Boys newly admitted into one large young offenders' institution, were consecutively interviewed individually and completed the MAYSI‐2, the Youth Self Report (YSR), which capture similar syndrome scales – and the Kiddie Schedule for Affective Disorders and Schizophrenia (K‐SADS), which allows for making psychiatric diagnoses. Results Two hundred and six boys, of average age 16.5 years, completed all assessments. According to the K‐SADS, co‐morbidity of psychiatric disorders was high (80% of the sample). The MAYSI‐2 showed good convergent validity but poorer discriminant validity with the YSR. The MAYSI‐2 and YSR corresponded with both conceptually and non‐conceptually relevant diagnostic domains. Conclusions The poor ability of the MAYSI‐2 and YSR to discriminate and specify disorders is likely to reflect the high rates of co‐morbidity. The fact that 90% of the participants reached the caution cut‐off for any scale on the MAYSI‐2, while suggesting its limited use as a screening tool for this sample, is probably best reflective of the high levels of psychopathology of incarcerated young people in England and Wales since particular efforts to divert as many as possible from custody. A more holistic and comprehensive approach to assessing health needs on admission into custody may be necessary for such a population. Copyright © 2014 John Wiley & Sons, Ltd.